Gemelli and his travel to the Philippines - Manzano, David (2013)
Giro del Mondo’s Volume V, by G. Francesco Gemelli Careri (1700), dedicates two books to describe several events which took place in the Philippines in 1696 as observed by the traveler. Our main goal will be to write a historical analysis of his account, underlining the importance of the Manila Galleon in the political, economic, and social life of the Philippines at the end of 17th century.
Keywords: Galleons -- Manila; Event history analysis -- -Philippines